2018
DOI: 10.20897/ejosdr/2668
|View full text |Cite
|
Sign up to set email alerts
|

Medical Waste Management is Vital for Safe Town Development: An Incident Study in Jessore Town, Bangladesh

Abstract: Health care institutions (HCIs) generate waste which can causes various injuries and infections to the patients, healthcare workers and also causes harm to the surrounding environment. Medical waste management (MWM) is vital for safe town development and the misconduct of medical waste may be a significant risk factor for the infectious diseases diffusion on our environment. The study carried out on 22 HCIs included public hospital, diagnostic centers, private hospitals and clinic in Jessore town of Bangladesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…A study performed in Jashore, Bangladesh by Som U, revealed 48.3%, 52.3% and 39.2% of sharp items, infectious and recyclable general wastes distinctively were not segregated in correct color coded bin.So their practices were similar to present study although COVID-19 waste was more hazardous (13).…”
Section: Resultssupporting
confidence: 85%
“…A study performed in Jashore, Bangladesh by Som U, revealed 48.3%, 52.3% and 39.2% of sharp items, infectious and recyclable general wastes distinctively were not segregated in correct color coded bin.So their practices were similar to present study although COVID-19 waste was more hazardous (13).…”
Section: Resultssupporting
confidence: 85%
“…This result also shows that there are no relationships between communication and collaboration, practice of waste management, supervision and staff monitoring and training and education, with effective medical waste management. The rejection of the relationship between training/education of medical staff and effective waste management in Bangladesh stem from various factors: the majority of garbage handlers in Bangladesh come from poorer socioeconomic backgrounds, have larger families, and possess less education and experience (Som & Hossain, 2018). However, Lakbala & Lakbala (2013) academic attainment and MWM training.…”
Section: Discussionmentioning
confidence: 99%
“…Other health hazards associated with improper HCWM are chemical burns from disinfection, radiation burns, thermal injuries from open burning, and incineration. High blood pressure, vomiting, headache, heart pain, and cough have also been associated with HCW handling [23]. Landfills can become breeding sites for disease-carrying organisms.…”
Section: Impacts Of Poor Hcwmmentioning
confidence: 99%
“…The availability of waste disposal materials is fundamental to waste management [20]. Studies in Bangladesh [23] and Uganda [43] revealed a lack and improper use of personal protective equipment (PPE) such as gum boots, gloves, caps, and overall coats. Elsewhere, studies of private healthcare facilities in Nigeria [48] and Ethiopia [35] reported high use of PPE in waste handling.…”
Section: Availability Of Hcwm Materialsmentioning
confidence: 99%
See 1 more Smart Citation